2022
DOI: 10.1021/acsnano.2c06560
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Programming of Nanovaccines for Lymph Node-Targeted Delivery and Cancer Immunotherapy

Abstract: In situ cancer vaccines consisting of antigens and adjuvants are a promising cancer treatment modality; however, the convenient manufacture of vaccines in vivo and their efficient delivery to lymph nodes (LNs) remains a major challenge. Herein, we outline a facile approach to simultaneously achieve the in situ programming of vaccines via two synergetic nanomedicines, Tu-NPFN and Ln-NPR848. Tu-NPFN (∼100 nm) generated a large number of antigens under an alternating magnetic field, and Ln-NPR848 (∼35 nm) encapsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Jin et al demonstrated an in situ cancer vaccine-based approach; in their study, they designed in situ vaccines by combining two synergetic approaches. First, ferrimagnetic nano cubes were encapsulated into an amphiphilic polymer, which generates the antigens by a magnetic field and destroys the primary tumor, and another polymeric nanoparticle coated with adjuvant R848 (resiquimod) delivers the formed antigens to the lymph node, activates the APCs and creates an antitumor immune response to distant tumors [ 139 ]. Li et al conducted another in situ based study.…”
Section: Cancer Immunotherapy Delivery Methodsmentioning
confidence: 99%
“…Jin et al demonstrated an in situ cancer vaccine-based approach; in their study, they designed in situ vaccines by combining two synergetic approaches. First, ferrimagnetic nano cubes were encapsulated into an amphiphilic polymer, which generates the antigens by a magnetic field and destroys the primary tumor, and another polymeric nanoparticle coated with adjuvant R848 (resiquimod) delivers the formed antigens to the lymph node, activates the APCs and creates an antitumor immune response to distant tumors [ 139 ]. Li et al conducted another in situ based study.…”
Section: Cancer Immunotherapy Delivery Methodsmentioning
confidence: 99%
“…The ideal cancer vaccine to achieve efficient anti-tumor effects could have them targeted to immune organs to induce targeted activation in addition to conventional TAAs and immune adjuvants. Among the many immune organs, lymph nodes reside a large number of APCs and T cells, which are the front-runners for antitumor immunotherapy [ 48 , 49 ]. Sun et al [ 50 ] used B16-F10 tumor cell membranes to wrap aluminum phosphate nanoparticles and CpG to make nanoparticles APMC.…”
Section: Cell Membrane Modified Nanomaterialsmentioning
confidence: 99%
“…[36] In the last decades, nanotechnology has been used to enhance the effectiveness of the immune response to tumor vaccines by delivering tumor antigens to LNs using nanoparticles (NPs)-based carriers. [37][38][39] NPs with positive surface charges have the ability to adsorb tumor antigens and NPs can also codeliver tumor antigens and immunomodulators to further activate immune system. [40,41] Moreover, in previous studies, it was demonstrated that spherical NPs with a particle size of between 25-50 nm can rapidly reach DLNs through tissue barriers; NPs larger than 100 nm need to be transported to LNs via DCs, while NPs larger than 500 nm do not efficiently reach LNs owing to macrophages clearance.…”
Section: Introductionmentioning
confidence: 99%